Przedstawienia i symbolika roślin w poezji Pindara - Stuligrosz, Magdalena (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The extensive use of plant motifs is at the heart of Pindar’s poetic images and metaphors. In his epinicions, the poet uses the symbolism of plants associated with Olympian and Pythian games to praise the victor and to show the importance of his achievement. The olive and laurel wreaths with which the victorious athletes are crowned become symbols of excellence and of the immortal fame accompanying human achievements, which is guaranteed by the poet’s song. Spring flowers such as roses and violets have a specific ritual meaning in Pindar’s cult songs, especially in his dithyrambs, where they symbolize vitality and rebirth. Aside from the plants typical of Greek flora, the Theban poet mentions those with miraculous properties, distinguished by their golden colour, which are associated with the divine and characteristic of sacred places and mythical landscape with paradisical connotations. Therefore, the symbolic meaning of floral imagery in Pindar’s Laments and in some passages from his victory songs cannot be recognized without taking into account its eschatological context.